Combustion performance and emission characteristics of diesel engine fueled with iso-butanol/biodiesel blends. (15th May 2020) - Xiao, Helin; Guo, Fengyun; Wang, Ru; Yang, Xiaolong; Li, Shengjun; Ruan, Jie
Abstract: The combustion performance and emission characteristics of a diesel engine powered by iso -butanol/biodiesel blends were experimentally studied under different load conditions at the engine speed of 1800 rpm. It was found the blending with iso -butanol improved the evaporation and atomization performances of biodiesel and altered the combustion characteristics of the blended fuels. The ignition delay of tested fuels was prolonged with the rise of iso -butanol ratio. However, the combustion duration would decrease with the rise of iso -butanol ratio when the engine loads exceeded 0.38 MPa brake means effective pressure (BMEP). For regulated gaseous pollutants, iso -butanol/biodiesel blends intensified HC emissions under the entire engine load conditions and reduced CO emissions except at 0.13 MPa BMEP. NOx emissions were increased significantly by blending iso -butanol at moderate and high engine loads. As for particulate matter (PM) emission, the peak number concentration of particles in size <10 nm increased, but that of larger particles decreased gradually with the rise of iso -butanol ratio. The geometric mean diameter (GMD) of particles decreased with the rise of iso -butanol blending ratio. Moreover, the blended fuel with 30% iso -butanol reduced the particulate mass concentration significantly under both 0.88 and 1.13 MPa BMEP engine loads.